Design and FEM analysis of high‐power density C‐core permanent magnet transverse flux generator with reduced PM volume. Issue 4 (23rd November 2022) - Muhammad, Ali; Khan, Faisal; Ullah, Basharat; Milyani, Ahmad H.; Azhari, Abdullah A.
Abstract: Transverse flux machines are made up of armature coils wound in a circular direction and surrounded by armature cores. This configuration enables machines to be designed for multi‐pole structures while maintaining a simple coil geometry regardless of the pole count. As a result, these machines generate more torque and power density than most of the machines with windings wound around teeth and inserted into slots. However, transverse flux machines continue to face manufacturing difficulties because a large number of relatively small permanent magnets are required. Thus, a permanent magnet transverse flux generator (PMTFG) is designed with half the magnets on the rotor in comparison with a regular design while generating 18% better power density at the same size and excitation conditions. After proper parameter selection, the electromagnetic performance of the design is examined, and the viability of the design is verified using a three‐dimensional finite‐element model (FEM). Further analyses were carried out to examine the effect of stator core material and air gap length on the performance of PMTFG. Furthermore, a prototype of the proposed topology is built, which validates the performance obtained through FEM. Abstract : A PMTFG is proposed and analyzed in this paper. The proposed topology consists of 8 semi‐closed stator cores having pole shoes to enhance flux linkage and reduce the PM volume. Using viable space in stator cores, the double coil is used in armature winding to enhance back‐emf and make it a fault‐tolerant.